Awake venovenous extracorporeal membrane oxygenation and survival - Rottmann, Felix A.; Zotzmann, Viviane; Supady, Alexander; Noe, Christian; Wengenmayer, Tobias; Staudacher, Dawid L. (Frontiers in Medicine, 2024)
Objectives: Deep sedation on the ICU is linked to poor outcome. This study investigated the link between Richmond Agitation-Sedation Scale (RASS) and outcome in venovenous extracorporeal membrane oxygenation (V-V ECMO). Methods: We performed a secondary analysis of a single-center V-V ECMO cohort. RASS was used as a surrogate measure of sedation depth, patients with a score ≥-1 were considered awake. V-V ECMO durations below 24 h were excluded. Primary endpoint was 30-day survival. Secondary endpoints were hospital survival and weaning from both ventilator and ECMO therapy. Results: A total of 343 patients were reanalyzed. The median age was 55 years and 52.2% (179/343) survived for 30 days after ECMO cannulation. Median duration of ECMO was 7.9 (4.7-15.0) days and the median duration of mechanical ventilation after ECMO cannulation was 11.8 (6.7-23.8) days. In the whole cohort, median RASS on day one and seven after ECMO were -4 (-4 to -1) and -3 (-4 to 0), respectively. ECMO survivors consistently had significantly higher RASS scores during the first seven days of ECMO compared to non-surviving patients (p<0.01). On day two after ECMO, survival of awake patients (i.e. RASS ≥-1) was significantly better compared to sedated (i.e. RASS -4 to -2; OR 2.20 (1.28-3.71), p<0.01) or unresponsive patients (i.e. RASS -5; OR 2.27 (1.15-4.64), p=0.02). The survival benefit of awake ECMO was consistent from day two to seven. Patients awake at least once during ECMO showed higher 30-day survival rates (64.4% vs. 39.6%, OR 2.75 (1.77-4.24), p<0.01). Conclusion: see manuscript